Implementation of the Red and White Village Cooperative program in Bekasi City: opportunities, challenges, and strategies - Muhammad Randi Yudhistira (CV. Literasi Indonesia, 2026)
Red and White Cooperative Program is a national initiative launched on July 21, 2025, to strengthen the people's economy based on villages and villages. As a buffer city with the highest GDP in West Java (IDR 129.35 trillion in 2024) but facing a spike in poverty (129,540 people as of March 2025), Bekasi City recorded implementation achievements that lag behind the surrounding areas. This paradox is even more prominent considering that KKMP at the village level should have a greater chance of implementation because it does not intersect with Village-Owned Enterprises (BUMDes) as happens at the village level. This research aims to identify the main opportunities and challenges and formulate a strategy for the implementation of the KKMP program in Bekasi City. Using a qualitative approach with a case study method, data was collected through in-depth interviews with six key informants as well as qualitative questionnaires to 10 respondents from six cooperatives. The analysis uses a SWOT framework quantified through the IFAS-EFAS matrix, based on the theory of Rogers' Innovation Diffusion (2003) and the Implementation of the Van Meter & Van Horn Policy. IFAS-EFAS mapping puts KKMP at coordinates (−0.289; −0.151) in the W-T Quadrant, with five recommended integrated strategies: policy advocacy, strengthening legality, cluster-based organizational structuring, operational efficiency, and member market segmentation.